Estimated weight on goats with a commercial weighing tape and thoracic perimeter. - Chacón-Hernández, Pablo; Boschini-Figueroa, Carlos (Agronomía Mesoamericana, 2016)
The objective of this paper was to determine the technical viability of using a weighing tape to measure the pectoral circumference and estimate the body weight of goats. The study took place in the Alfredo Volio Mata Experimental Station in the University of Costa Rica, during the month of February 2015, by measuring the weight with a scale, a calibrated weighing tape and the thoracic diameter of sixty female goats. The data was adjusted through polynomial equations from rst to third degree. The thoracic diameter was used to determine the living weight of the goat population analyzed. Significant differences were found (p<0,05) when using the calibrated tape and the scale to determine the weight, with the obtained values of an average of 48,62kg y 39,99kg, respectively. There were differences (p<0,05) in the average of the weight depending on the age with results of 24,40kg in animals less than a year old, 40,39kg for the ages from one to three and 57,25kg for animals older with more than three years of age. The rst degree lineal regression, presented a good adjustment in the thoracic diameter and living weight( r2 = 0,88), with the values of ß0 and ß1 of -50,84 y 1,11, respectively.